Incumplimiento de las garantías del debido proceso en la sustanciación de los juicios de alimentos y sus efectos jurídicos. - GAVILEMA ARÉVALO, BERTHA Enriqueta (2009)
The present investigation understands a juridical study, of the problem that arises for the no fulfillment of the Guarantees of the Due Process in the procedure of the Trials of Foods. Guarantees that are contemplated in the Constitution of the Republic of the Ecuador, and in the Code of the Childhood and Adolescence. This no fulfillment has generated in the Ecuadorian family; dissatisfaction and distrust in the juridical system, since it is attempted against their rights to the Due Process and to have a justice without delays. The no fulfillment of the benefit of foods and the late resolutions of the trials of foods in particular constitute a problem of serious consequences for the members of the family that wait to be assisted in the brevity of the time, but it doesn't happen this way, what demonstrates that that is not completed that specifies the I articulate 282 of the Code of the Childhood and Adolescence. The same one that refers to the duration of the process that cannot last but of fifty counted days from the citation with to the demand in first instance, neither but of twenty-five days from the reception of the process, as much in second instance as in the case of cassation, when not being fulfilled these terms the National Council of the Judicature it will sanction to the Judge and each one of the Secretaries Judges of the room corresponding with ticket of twenty dollars for every skilled day or fraction by day late, in the event of repetition the National Council of the Judicature applied the sanctions that it corresponds. In this context, with the application of the surveys and the interviews we have checked that the Guarantees of the Due Process are not completed regarding the time in which is carried out the process of the substantiation of the trials of foods, many of the times he/she is due to the ignorance of the Law and of the rights that attend us. The State of Right and the Due Process are the fundamental pillars of the modern State that consecrate and the man's rights like a citizen guarantee who tramps their rights the wheel of the history he/she will have gone back, it is pending for the State to watch over this action radius very closely. From the slopes of the Constitution, the Code of the Childhood and Adolescence, Civil Code, Code of Civil Procedure, also the modern doctrine one comes outlining the necessity to give to the “right of the foods” one guides more intense, a more effective protection, in order to find the satisfaction in the members of the disintegrated family, for different reasons.